PUSTAKAWAN SEBAGAI TENAGA PROFESIONAL - Yuhelmi, Yuhelmi (Universitas Lancang Kuning, 2014)
Some scientists say that people are in the global era now. Library has a strategic position in the community to still exist in the global era. So,, librarian must be professional on serving the users. In fact, not all librarians have been professional on their jobs. Some studies show that only small number of librarians in Indonesia have been professional. However there aresome points which can get some step to get librarians 'professionality, such as .focusing on their jobs, increasing their professionality, adopting information technology, and making networking.